A Possible Selves Perspective on Transitional Learning - Marsha Rossiter (Adult Education Research Conference, 2008)
The premise of this paper is that the possible selves construct offers a useful perspective for understanding adaptability, change, and transitional learning across the life span. Possible selves and transitional learning are outlined. Elements of a possible selves perspective on transitional learning are presented.
Keywords: transitional learning; possible selves